Effects on monoamine levels in rat CNS after chronic administration of cocaine - Alburgues, Mario; Wamsley, James (Investigación Clínica, 2013)
Â  We have previously reported time-dependent changes in the rat dopaminergic receptor system following chronic administration of cocaine (upregulation of cocaine, D1 and DA-uptake sites). We have now evaluated the effects of cronic cocaine exposure on the central catecholamine/indolamine neurotransmitter systems. Groups if rats were injected with cocaine (15 mg/kg, i.p., b.i.d.) or saline for 1, 3, 7, 14 or 21 days. Cortical and their primary metabolites using a HPLC-ECD method. Chronic administration of cocaine did not change the cortical and striatal concentrations of the neurotransmitters under study; except, for a transient increase in the cortical MHPG concentration on day 3. These results suggest that changes in the dopaminergic receptor system following chronic cocaine exposure are not due to changes in the neurotransmitter concentrations.